2013
DOI: 10.1093/jmicro/dft042
|View full text |Cite
|
Sign up to set email alerts
|

The potential for Bayesian compressive sensing to significantly reduce electron dose in high-resolution STEM images

Abstract: The use of high-resolution imaging methods in scanning transmission electron microscopy (STEM) is limited in many cases by the sensitivity of the sample to the beam and the onset of electron beam damage (for example, in the study of organic systems, in tomography and during in situ experiments). To demonstrate that alternative strategies for image acquisition can help alleviate this beam damage issue, here we apply compressive sensing via Bayesian dictionary learning to high-resolution STEM images. These compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
145
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 25 publications
0
145
0
1
Order By: Relevance
“…However, the last 40 years of protein crystallography and more recently the use of in-situ liquid stages to study chemical reactions in the (S)TEM [3], have shown that this beam damage effect can in most cases be mitigated by the use of extremely low-dose imaging (a dose rate of less than 0.1 electrons/angstrom 2 /s and a cumulative dose of less than 10 electrons/angstrom 2 ). In addition to simply lowering the dose through conventional means (changing the emission current and probe dwell time), more recent use of compressive sensing/in-painting methods for STEM has also been shown to lower the effective dose and dose rate [4]. Figure 1 shows a Z-contrast image obtained from an NU-1000 MOF [2] obtained from a probe corrected FEI 80-300kV Titan operating in the low-dose mode described above.…”
mentioning
confidence: 99%
“…However, the last 40 years of protein crystallography and more recently the use of in-situ liquid stages to study chemical reactions in the (S)TEM [3], have shown that this beam damage effect can in most cases be mitigated by the use of extremely low-dose imaging (a dose rate of less than 0.1 electrons/angstrom 2 /s and a cumulative dose of less than 10 electrons/angstrom 2 ). In addition to simply lowering the dose through conventional means (changing the emission current and probe dwell time), more recent use of compressive sensing/in-painting methods for STEM has also been shown to lower the effective dose and dose rate [4]. Figure 1 shows a Z-contrast image obtained from an NU-1000 MOF [2] obtained from a probe corrected FEI 80-300kV Titan operating in the low-dose mode described above.…”
mentioning
confidence: 99%
“…Technological limitations are also associated with obtaining images faster; in the case of the TEM low-dose imaging requirements exceed the framerate of the camera, while in STEM the hysteresis in the scan coils limits the overall scanning speed that can be obtained. To overcome some of these limitations it is possible to use a set of image reconstruction methods such as compressive sensing and in-painting [1,2] to reduce the overall number of readouts/pixels in the TEM/STEM images/movies and lower the overall electron dose while at the same time increasing the speed of the image and reducing the overall size of the dataset acquired [3,4].An example of the use of in-painting to recover pixels in a sub-sampled STEM image is shown in Figure 1. Here the image is sub-sampled after acquisition and recovered to demonstrate that high resolution images typically acquired in a TEM/STEM are over-sampled.…”
mentioning
confidence: 99%
“…
Compressive sensing approaches are beginning to take hold in (scanning) transmission electron microscopy (S/TEM) [1,2,3]. Compressive sensing is a mathematical theory about acquiring signals in a compressed form (measurements) and the probability of recovering the original signal by solving an inverse problem [4].
…”
mentioning
confidence: 99%